Strategi Komunikasi Politik “Nyantri” Prabowo Subianto dalam Memenangkan Pilpres 2024 - Hafid, Hafid; Jannah, Siti Raudhatul; Jauhari, Minan (Jurnal Riset Komunikasi (JURKOM), 2024)
Abstract The 2024 general election involved three candidates—a couple of presidential candidates and vice presidents. They're struggling to win the number one seat in the Republic. Each one of them uses the best political strategy to gain the people's sympathy. One of them is Prabowo Subianto, a presidential candidate who has "sustained" for three consecutive elections and has not even emerged as a winner. The study aims to understand Prabowo Subianto's political communication strategy as a presidential candidate to gain the support of the Santri and Kiai Pondok Pesantren as one of the national voices. This research uses Robert M. Entman's framing analysis with a library approach, i.e., online media, as an object of research carried out in the period prior to the campaign period until the campaign was completed. The results of the research show that Prabowo's political communication strategy for gaining the support of Kiai and the hostel centers is using three patterns of imagery. First, pure publicity, namely, Prabowo, popularized itself with a number of supporters and won the Gibran couple. Second, Free Ride Publicity (Prabowo) visited the Pondok Pesantren and was named Santri Indonesian friend by the Santri and Kiai. Third, Paid Publicity called on the media to cover and broadcast the declaration of Gibran's couple at the same time as the perpetual fund campaign. Keywords: Communication Strategy, Nyantri Politics, General Election, President